Aging, society, and the life course - Morgan, Leslie A.; Kunkel, Suzanne (Springer Publishing Company, LLC, 2016)
"[This] book's unfading preoccupation with social context, social processes, and social structures distinguishes itself and greatly contributes to the discourse in gerontology."--The Gerontologist. This classic text, now in its fifth edition, is distinguished by its emphasis on social context, social processes, and social structures as part of a broader understanding of the sociology of aging and the life course. Presenting an objective view of the realities of aging, both positive and negative, the book examines aging from micro/macro, personal, community, societal, and global perspectives